Validation of Malay Gender Role Conflict Scale for Adolescents - Mansor, Noorazida Zaharah; Othman, Zahiruddin; Yaacob, Mohd Jamil; Yasin, Mohd Azhar Mohd (Japan International Cultural Exchange Foundation, 2016)
Background: Living in a multiracial country undergoing rapid modernization with strong influence of Western media, exposed the Malaysian adolescents to conflicting gender role messages leading to potential gender role conflict. Objectives: This study aimed to validate the Malay Gender Role Conflict Scale for Adolescents (GRCS-AM). Methods: The GRCS-A was translated into Malay language and administered to 91 secondary school students in Kubang Kerian in July 2012. Results: The internal consistency coefficients of each subscale and the total scale were good with restricted affection between men 0.58; restricted emotionality 0.65; conflict between work, school, and family 0.64; need for success and achievement 0.62; and total scale 0.76. Conclusion: The GRCS-AM is a valid and reliable tool for assessment of gender role conflict in Malaysian adolescent population.